The Role of The Notary Honorary Assembly in Law Enforcement Following The Change of Article 66 of Law No. 30 Of 2004 on Notary Positions - Annisa Ayu Rachmayanti (Authentica, 2020)
The role and function of the Notary has experienced very rapid progress other than because of the very high community needs but also awareness of legal certainty related to an engagement. Notaries in carrying out their duties and positions are bound by the rules of office and are also bound by a code of ethics as a guide to the behavior of the Notary profession. This supervision is carried out by institutions that have been given the mandate based on applicable laws. The data used are secondary data and primary data as a complement to secondary data. The method used in this research is the normative juridical approach. The research results obtained by the Notary Honorary Council have a role in the supervision, guidance and protection of the notary public. Enforcement of law includes the role of supervision carried out by giving approval or rejection of the summon of the Notary and photocopy of a notary deed due to a request from the investigator or judge. Keywords: Role, Notary Honor Council, Law Enforcement